Treatment of nosocomial pneumonia: an experience with meropenem - Santos Sigrid S.; Machado Flavia R; Kiffer Carlos R. V.; Barone Antonio A. (Brazilian Journal of Infectious Diseases, 2001)
This study aimed at evaluating the efficacy and safety of meropenem as first choice treatment for nosocomial pneumonia (NP) in intensive care units (ICU) in Hospital das Clínicas (HC) - University of São Paulo; a hospital with high incidence of antimicrobial resistance. Prospective, open, and non-comparative trial with meropenem were done in patients with ventilator-associated or aspiration NP in 2 ICUs at HC - University of São Paulo. Etiologic investigation was done through bronchoalveolar lavage and blood cultures prior to study entry. Twenty-five (25) critically ill patients with NP were enrolled (mean age 40 years). Ventilator-acquired pneumonia was responsible for 76% of cases and aspiration NP for 24%. Specific etiologic agents were identified and considered to be clinically and temporally responsible for NP in 11 (44%) patients. A. baumanii was responsible for 6 cases (55%), P. aeruginosa for 3 (27%), and S. aureus for 2 (18%). At completion of treatment, 19 patients (76%) showed either cure (48%) or improvement (28%) after use of meropenem therapy. Mortality was 12% at the end of therapy (8% after excluding 1 non-evaluable patient). After 4 to 6 weeks of follow-up, 12 (48%) patients had improved or been totally cured, and overall mortality was 24%. Clinical complications were observed in 11 patients (44%), with none of them definitely related to the study drug. Meropenem as monotherapy was effective and well-tolerated in most NP patients in our ICU. The low mortality rate in this study might have been due to first choice use of this drug. Controlled, drug comparative clinical trials are needed to support this preliminary observation.